Communities and tree-species preferences of birds in traditional agroforestry system in Meru Betiri National Park - Agung Sih Kurnianto; Luhur Septiadi; Puji Firmansyah; Nilasari Dewi (The East Java Biological Society, 2022)
Agroforestry is a critical component of providing primary habitat for birds. Meru Betiri National Park (MBNP) establishes a diverse array of ecologically and economically significant trees while allowing local residents to farm beneath them, resulting in the formation of a complex agroforestry system. The purpose of this study is to examine bird communities and their tree-species preferences across tree height levels in MBNP's traditional agroforestry system. For vegetation analysis, we used the circle method, and for bird data collection, we used the point count method in a single circle approach. For both vegetation and bird communities, the ecological indices (the important value index, Shannon-Wiener diversity index, Margalef species richness index, and evenness index) were calculated. Birds' ecological roles and activity preferences were analyzed using principal component analysis and presented in stratified tree height levels. The results indicated that insectivores’ birds are the primary insect predators in the traditional MBNP agroforestry system (11 out of 16 bird families). Artocarpus heterophyllus was the most frequently visited tree species out of seven, which may have significant ecological value (for bird diversity) and economic benefits (for avitourism). Finally, one can deduce that the majority of bird activity occurs between 4 and 20 meters above the ground.